Bringing children and older people together through food: the promotion of intergenerational relationships across preschool, school and care home settings. Issue 2 (2nd March 2022) - Jones, Mat; Ismail, Sanda Umar
Abstract : Purpose: This paper aims to explore how food-focused social activities are a route for promoting intergenerational relationships, well-being and dietary benefits among residents in care homes and children in preschool/schools. Design/methodology/approach: Using a case study methodology, this study undertook staff-focused research on a 26-month UK programme in 12 partnership clusters, involving a range of growing, cooking, eating and community activities. Findings: Staff reported benefits for older people, including improved mood, surfacing positive memories, new personal connections and relief from feelings of boredom and loneliness. Children were reported to develop in-depth relationships, greater empathy and overcame negative preconceptions. Food-based activities enabled all parties to express caring and nurturing in tangible and often non-verbal ways. Originality/value: Food-based activities appear to have specific material and emotive characteristics that resonate with the intergenerational interests of older people and children. Using mainly in-house resources, this study showed that it is feasible to generate novel food-based practices between children's education and care home sectors. A "test-and-learn" programme model is recommended, given sensitivities and complexity associated with food-based activities and the limited organizational capacity of care home and early education service providers.